Desempenho e comportamento de novilhas em tifton 85 com diferentes níveis de suplementação - Martini, Ana Paula Machado (2018)
The objective of this study was to identify which variables of the productive parameters of the pasture, animal performance, ingestive behavior and displacement patterns explain most of the results among the levels of supplementation offered to heifers finished in Tifton 85 (Cynodon dactylon). Principal component analysis was used to identify which variables were relevant. In the analysis, the variables forage mass, canopy height, rate of forage accumulation, forage on offer, stocking rate, average daily gain, body weight, body condition score, grazing time, idle time, number of feeding stations/day, time per feeding station, bite rate/day, leaf blades mass, leaf allowance and leaf blade: stem ratio explained from 77.1 to 80.5% of the total variation of the results. Heifers who received 1.2% of supplement had higher weight, body condition score and average daily gain. Higher stocking rate and forage mass were verified in the treatment in which heifers received 0.8% of supplement, while greater forage on offer was observed in the treatment with 0.4% supplement. High rate of forage accumulation and canopy height was verified in the treatment in which heifers were exclusively kept on pasture. Heifers receiving 0.4% supplementation visited more feeding stations, while heifers who received 1.2% supplement remained longer in feeding stations. The level of 0.8% of supplementary did not influence the variables evaluated. Termination of heifers exclusively on Tifton 85 grazing is not feasible due to poor animal performance. Displacement patterns and ingestive behavior of heifers receiving or not supplementation are influenced by the structural characteristics of the pasture.